The Application of Gamification in Entrepreneurship Learning to Enhance Motivation and Business Creativity for Students - Ratna Puspita Dewi; Peri Puarag (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study addresses low student engagement and high levels of boredom in entrepreneurship courses that rely heavily on one-way PowerPoint-based lectures. Preliminary observations in-dicated that 80% of students experienced low motivation and difficulty generating innovative business ideas. The purpose of this research was to examine the effect of gamification on student learning motivation and business creativity.A quantitative approach was employed using a pre-experimental (One-Group Pretest–Posttest design). The sample consisted of 25 students selected through total sampling. Gamification elements, including: points, badges, and leaderboards, were integrated into the learning process to replace conventional lecture methods.The findings indicate that the implementation of gamification significantly trans-formed student learning behavior and classroom dynamics. Students shifted from passive disengagement, characterized by limited interaction and high distraction levels, to proactive participation. Verbal interactions increased substantially, moving beyond administrative ques-tions toward meaningful business discussions. Students demonstrated heightened engagement and responsiveness during learning activities. The gamified learning environment also fostered a safe space for creative experimentation, enabling students to take entrepreneurial risks without fear of academic or financial failure. Improvements were observed across key di-mensions of business creativity, including fluency, flexibility, originality, and elaboration. The study concludes that gamification is an effective pedagogical strategy for enhancing student motivation and business creativity in entrepreneurship education. By transforming learning from a passive knowledge-transfer model into an experiential and interactive process, gami-fication supports the development of an entrepreneurial mindset among digital native students.